Political Participation of Fishermen Community Voters Amidst COVID-19 in the Local Election - Risman, Risman; Muhiddin, Amir; Hartaman, Nursaleh (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2023)
This study examines fisherman community voters' political engagement in Covid 19 in the 2020 Regional Head Election in Tritiro Village, Bontotiro District, Bulukumba Regency. This qualitative research method analyses primary and secondary data using interview, observation, and documentation. According to the study, (1) Active Participation: The fishing community participates in the post-conflict local election by campaigning for certain candidates openly, placing banners for candidate pairs, socialising the programme for the next 5 years if mandated by the community, and most of the fishing communities choose one Paslon because of the 4 existing candidates, one may change and (2) Passive Participation: the fishing community participates passively because the problem occurs almost every general election and events have not been adequately analysed for the next participant. First, political parties' candidates are old. (2) campaign promises are not fulfilled with political realities, (3) post-conflict local election organisers lack socialisation, (4) candidate candidates are considered too much talk and not realised after taking office, and (5) the community participates passively because each community has a different perspective. (6) There are more pressing issues and (3) the Abstain group (Golput) or apathetic groups: Fishing communities rarely skip district head elections in Bulukumba Regency this year. Even if fishing villages are apathetic and think an election is pointless, they believe their one vote cannot influence the outcome.